189k views
0 votes
How can I simplify/rewrite the 1st(top) equation into the 2nd(Botton),please show a step by step solution.​

How can I simplify/rewrite the 1st(top) equation into the 2nd(Botton),please show-example-1

1 Answer

3 votes

Answer:

see below

Explanation:


-2(4 - (x)/(2) )^(5) + C

Think of the above as:


-(2)/(1) *
((8)/(2) - (x)/(2) )^(5) + C

=
-(2)/(1) *
((8 - x)^(5))/(2^(5)) + C

=
-(2)/(1) *
((8 - x)^(5))/(32) + C

=
-(1)/(1) *
((8 - x)^(5))/(16) + C

=
(-1(8 - x)^(5))/(16) + C

=
((-8 + x)^(5))/(16) + C

Can flip it around to be...


((x - 8)^(5))/(16) + C

User MaVCArt
by
5.2k points